Effects of Cervical Preparation Design on Fracture Strength of Lithium Disilicate Endocrowns in Endodontically Treated Molars: A Systematic Review - Hamid Reza Zaker Jafari; Mahsa Koochaki; Mohammad Sadegh Mohammaditabaar; Amirreza Hendi (Wolters Kluwer Medknow Publications, 2024)
Introduction: We aimed to assess the effect of the type of finish line and ferrule on fracture resistance of lithium disilicate endocrowns. Methods: The literature search was done in Pubmed, Scopus, Dimensions, and Web of Science till August 2023, without language restrictions, using the following terms: ("endocrown" OR "endocrowns" OR "endo-crown" OR "endodontic crown" OR "endodontically treated crown") AND ("preparation" OR "preparation design") AND "fracture resistance" AND "lithium disilicate" AND "molars". Grey literature was similarly investigated via WorldCat, Open Grey, and Google Scholar. An artificial intelligence-powered software, SWIFT-Review, is employed for text mining at the selection stage. Risk of bias among included studies according to the QUIN was also assesed. Results: From 49 articles resulted from a systematic search of databases, four of them qualified as eligible studies to be reviewed. All included articles were reports of in vitro studies and their outcome were controversial. Koosha et al. and Naji et al. reported non-significant differences between specimens with ferrule and shoulder finish lines and butt-joint finish lines. However, Einhorn et al., indicated that restorations with ferrule exhibited significantly higher fracture resistance than butt-joints. Amin et al., concluded ferrule design would improve fracture resistance. All included studies in the review are evaluated as medium risk. Furthermore, no study had considered blinding in the methods. Conclusion: Outcomes of included studies were controversial, and concerning the methodological limitations of included studies it is not that easy to reach a clear and definitive conclusion.